Diversity of Aspergillus isolates and selection of an isolate with high β-fructofuranosidase activity that is native to the Peruvian coast - Gutarra Castillo, Boris (2017)
In order to obtain a native isolate with high β-fructofuranosidase activity (FFase), a preliminary selection of 44 isolates, predominantly formed by Aspergillus niger (72%), was performed among 167 isolates of Aspergillus native to the Peruvian coast (Casa grande, Cartavio, Paramonga and Tacama). In addition, genetic diversity was studied using molecular markers, Inter Simple Sequence Repeats (ISSR). The FFase activity of these 44 isolates was compared and the isolate which showed the highest fructosyltransferase (FTase) activity was identified molecularly at the species level by DNA sequencing. Cluster analysis indicated 16 sub-genetic groups of which 11 of them were morphologically identified as Aspergillus niger. Samples from Paramonga showed the highest genetic diversity as explained by the Shannon diversity index (I= 0.21). No positive association was found between the genetic diversity of populations and FFase activity. Isolates PR-151, PR-144 and PR-142 showed the highest FFase activity in 5 consecutive evaluation generations, PR-142 being the most active with a total FFase activity of 11,248 (U.L-1) and 6.17 g/L of biomass indicating a great biotechnological potential for the synthesis of prebiotics. The molecular identification at the species level confirmed that PR-142 belongs to A. niger lineage.